The Effect of Servicescape on Revisit Intention through Customer Satisfaction as a Mediating Variable at Kopi Konnichiwa Tomang, West Jakarta - Denissa Aurelia; Lamtiar Hema Malini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although servicescape has been widely recognized as a key determinant of customer experience in service settings, its role in strengthening revisit intention through customer satisfaction remains important to examine in the coffee shop industry. This study aims to analyze the effect of servicescape on revisit intention with customer satisfaction as a mediating variable at Kopi Konnichiwa Tomang, West Jakarta. This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to customers who had visited Kopi Konnichiwa Tomang and were selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the direct and indirect relationships among servicescape, customer satisfaction, and revisit intention. The findings indicate that servicescape has a positive and significant effect on customer satisfaction. Customer satisfaction also has a positive and significant effect on revisit intention. In addition, servicescape has a significant indirect effect on revisit intention through customer satisfaction, confirming the mediating role of customer satisfaction. This study concludes that improving the quality of servicescape can enhance customer satisfaction, which subsequently increases customers’ intention to revisit Kopi Konnichiwa Tomang. The findings contribute to service marketing literature by reinforcing the importance of the physical service environment in shaping customer loyalty and provide practical implications for coffee shop managers in designing comfortable, attractive, and experience-oriented service settings.